Digital learning needs of elder people: a review study - Franco-Caballero, Pablo Daniel; Leiva-Olivencia, Juan José; Matas-Terrón, Antonio (My University, 2015)
This paper shows the conclusion from a review study about the digital learning needs of elder people. In developed countries a process of population ageing is occuring. The interesting feature of this ageing process is that despite their elderly status, their physical and mental healthiness are optimal and their quality of life is high, as is their economic capacity to access to goods and services. This reality is changing the developed societies structure and their identity. Specifically, the extension of productive activity by people as well as an extension of leisure culture. Literature consulted highlights the productive life extension needs be supported by a learning process throughout whole life. Also, leisure culture requires people to acquire and develop the digital skills needed in order to access to new media entertainments. Furthermore, critical ability in regards to selection and consumption of these goods and services needs to be active. The different papers and documents reviewed have been analyzed into a discussion group. The main conclusions are: - The learning content must be defined from specific learning needs from elder people. - The hardware and sets must be adapted to perceptive abilities elder people. - Software must be user friendly and efficient. Finally, it is necessary to develop a theoretical framework in order to gain enough support to design teaching activities. This framework will guide the performance of teaching actions as well as the programs evaluations.
Keywords: Ancianos; Alfabetización tecnológica; Elder people; Digital literacy